Characteristics of power growth of a multidimensional series of exponents - Makarov, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The behavior of sums of multidimensional series of exponents near the boundary of the region of absolute convergence is studied.